Negative effect of varicocele on sperm mitochondrial dysfunction: A cross-sectional study - Mahshid Elahi; Vida Hojati; Mahmoud Hashemitabar; Mahsa Afrough; Hossain Mohammadpour Kargar; Maryam Dastoorpoor (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Varicocele is an abnormal dilation and enlargement of the scrotal venous pampiniform plexus that impairs normal blood drainage and finally leads to infertility if not treated. Objective: This study aimed to figure out the impact of mitochondria status through the mitochondrial membrane potential (MMP) and adenosine triphosphate (ATP) assessment and its correlation with semen parameters to illuminate the impact of sperm mitochondria healthiness on normal sperm functionality. Materials and Methods: This analytical cross-sectional study was conducted with 100 men including 50 cases in the normozoospermic group (normal) and 50 in an infertile group with the non-varicocelectomy operation (varicocele) referring to Infertility Research and Treatment Center, ACECR Khuzestan, Iran. Routine semen analysis was performed according to World Health Organization guidelines, DNA fragmentation index, the MMP assay, ATP content, and apoptosis were carried out for all samples. Results: The results showed that the concentration, progressive motility, normal morphology, MMP, and ATP contents of sperm in varicocele were significantly lower than the normal group. In addition, the sperm DNA fragmentation index was significantly higher in the varicocele group in comparison with the normal group. Conclusion: Reduction in MMP and ATP contents, besides the loss of sperm parameters quality and increase in sperm DNA fragmentation, were seriously implicating sperm mitochondria dysfunctionality in varicocele men.